Analysis of Factors Influencing Impulsive Buying Behavior and the Role of Influencer Marketing in Electronic Commerce - Pangestu, Raka; Hati, Sri Rahayu Hijrah (Universitas Batanghari Jambi, 2025)
This study aims to explore how external factors such as demand, interactivity, e-commerce anchor attributes, playfulness, perceived scarcity, immersion, and convenience affect the perception of enjoyment and involvement in impulsive buying behavior in e-commerce in Indonesia. A total of 393 respondents who have experienced and enjoyed the live streaming shopping feature and made purchases on one e-commerce platform were used. The analysis was carried out using SmartPLS 4.0. The results showed that e-commerce anchor attributes, playfulness, perceived scarcity, immersion, and convenience have a positive effect on the perception of enjoyment and interactivity which ultimately have a positive effect on impulsive buying behavior. However, one demand variable and the two convenience variables did not have a positive effect.